Edaphic Fauna Associated with Areas Managed under no-till with and without Terraces - Inara de Souza Stockmann; Dinéia Tessaro; Lucas da Silva Domingues; Jéssica Camile da Silva; Luis Felipe Wille Zarzycki; Ketrin Lorhayne Kubiak; Erivelto Folhato Tolfo (Brazilian Archives of Biology and Technology, 2024)
Abstract Conservation soil management systems can promote beneficial changes in the edaphic fauna, which is important in improving and maintaining soil quality. Hence, this study aimed to evaluate the edaphic fauna in two areas with soils managed under no-till with and without terraces for four years. The edaphic fauna was evaluated by installing 32 pitfall trapsin each experimental plot. After seven days, the traps were removed, and the sampled individuals were classified at the level of major taxonomic groups. Collembola, Acari, Formicidae, Coleoptera, and Araneae were the most abundant in both study areas. The mean abundance of the order Coleoptera stood out in the no-till system with terraces in 2021, while the orders Collembola and Acari were more abundant without terraces in 2019 and 2021, and 2021 and 2022, respectively. There was a greater abundance of organisms for both areas in 2021, with significant equitability in the no-till system with terraces. Thus, the results showed that only some groups are positively affected by mechanical erosion control.